The lucky lottery - Roy, Ron; Gurney, John Steven (New York : Random House, 2000)
Dink and his two friends help Lucky find the culprit who stole Lucky's winning lottery ticket.
"A Stepping Stone book."
Keywords: Lotteries; Mystery and detective stories